Association between blood inflammatory status and the survival of tuberculosis: a five-year cohort study - Ji, Yating; Xie, Qingyao; Wei, Wei; Huang, Zhen; Liu, Xuhui; Ye, Qi; Liu, Yanping; Lu, Xiaoyu; Lu, Yixiao; Hou, Renjie; Zhang, Qingping; Xu, Yanzi; et al. (Frontiers in Immunology, 2025)
BackgroundBlood inflammatory status is closely associated with tuberculosis (TB) progression. Emerging inflammatory indices from different leukocyte subtypes have become a prognostic hotspot for various diseases, yet their application in TB prognosis remains limited. This study aims to assess the impact of inflammatory status on TB patients’ prognosis and its potential as a prognostic indicator to optimize prognostic assessment and therapeutic strategies.MethodsThis study included 4027 TB patients admitted to a tuberculosis-designated hospital in Shenzhen from January 2017 to December 2022. Patients were classified into three inflammatory statuses (Q1-Q3) based on each index’s level. We conducted Cox regression and restricted cubic splines (RCS) analyses to evaluate the association between inflammatory status and unfavorable outcome, subgroup analyses to understand heterogeneous associations among subpopulations, and receiver operating characteristic (ROC) analyses to evaluate the prognostic performance of inflammatory status on TB treatment outcomes.ResultsDuring 48991.79 person-months of follow-up involving 4027 patients, 225 unfavorable outcomes occurred. Multivariable Cox regression indicated that the Q3 levels of CAR, CLR, dNLR, NLR, SII, and SIRI increased the risk of unfavorable outcome by 45%-99% (HR: 1.45-1.99, all P<0.050), whereas ENR reduced the risk by 29% (HR: 0.71, P=0.040) compared to Q1. RCS curves revealed linear associations with unfavorable outcome that were positive for CAR, CLR, dNLR, SII, and SIRI, negative for ENR (all P for nonlinear>0.050), and nonlinear for MLR, NLR, and PNI (all P for nonlinear<0.050). Subgroup analyses identified heterogeneous associations across age, sex, BMI, comorbidities, and drug resistance (all P for interaction<0.050), with attenuated risk effects of CAR, CLR, dNLR, and SII in patients aged 30-60 years, male, BMI≥24.0 kg/m², smokers, retreatment cases, and those with tumor. ROC analysis demonstrated stable predictive performances of inflammatory status (AUC: 0.785–0.804 at 6-month, 0.781–0.793 at 9-month, and 0.762–0.773 at 12-month), and the combination of the inflammatory status significantly optimized the prognostic performance of the basic model (9-month AUC: 0.811 vs 0.780, P=0.024; 12-month AUC: 0.794 vs 0.758, P=0.013).ConclusionPretreatment blood inflammatory status effectively predicts the treatment outcome of TB patients. Our findings hold significant clinical value for TB patient management and warrant prospective evaluation in future studies.